Ortho-C–H Benzylation of Aryl Imines with Benzyl Phosphates under Cobalt–Pyphos Catalysis - Xu, Wengang (2015)
Ortho-C–H benzylation of aryl ketimines with benzyl phosphates is achieved with the aid of a catalytic system consisting of a cobalt(II) salt, a phosphine/pyridine bidentate ligand, and a Grignard reagent under room-temperature conditions, affording a variety of diarylmethanes bearing o-acetyl or -acyl groups in moderate to good yields. Owing to the versatility of the o-acetyl group, the reaction opens useful synthetic routes to polycyclic compounds such as unsymmetrical anthracene, anthracenone, and anthraquinone derivatives.